Lift procedure for long complex ano-scrotal fistula and review of literature - Kumar, T. Siva; Naresh, G.; Akther, Md. Jawed (International Surgery Journal, 2016)
Ano-rectal sepsis can be complicated by anal fistula during the acute phase of sepsis or within 6 months thereafter. An anal fistula is characterised by chronic purulent drainage or cyclical pain associated with abscess formation, followed by intermittent spontaneous decompression. A fistula-in-ano can be "simple" or "complex". The goal of surgical management is to effectively eradicate current and recurrent septic foci, associated epithelialized tracts and preserve continence. Study present a case of 22 year old male with long recurrent complex ano-scrotal fistula which was treated by ligation of the intersphincteric fistula tract (LIFT) procedure, preserving the anal continence without leaving any residual septic foci that may lead to recurrence.